An Open‐Label, Randomized, Pivotal Bioequivalence Study of Oral Rolapitant. Issue 2 (9th January 2019) - Zhang, Zhi‐Yi; Wang, Jing; Arora, Sujata; Lu, Sharon; Powers, Dan; Kansra, Vikram; Wang, Xiaodong
Abstract: Rolapitant, a selective and long‐acting neurokinin‐1 receptor antagonist, is approved in an oral formulation for prevention of delayed chemotherapy‐induced nausea and vomiting in adults. This pivotal open‐label, randomized, single‐dose, multicenter, parallel‐group study assessed the bioequivalence of a single oral dose of 180 mg of rolapitant administered in tablet (2 × 90‐mg tablets) or capsule (4 × 45‐mg capsules) form in healthy male and female subjects. Blood samples for pharmacokinetic analysis were collected predose and at times up to 912 hours postdose. The rolapitant tablet was considered bioequivalent to the rolapitant capsule if the 90% confidence intervals for the ratios of the geometric means for rolapitant, observed maximum plasma concentration (Cmax ), and area under the curve from time 0 extrapolated to infinity (AUC0‐∞ ) were within the 0.80–1.25 range. The pharmacokinetic profiles of the capsule group (n = 43) and tablet group (n = 44) were similar. The geometric mean ratios of Cmax and AUC0‐∞ were 0.99 (0.89–1.11) and 1.05 (0.92–1.19), respectively, establishing bioequivalence of the rolapitant tablet and capsule formulations. Both formulations were well tolerated, with a similar incidence of treatment‐emergent adverse events in the 2 groups.